Comparative analysis of unmanned aerial vehicle and conventional spray systems for the maize fall armyworm Spodoptera frugiperda (J.E. Smith) (Lepidoptera; Noctuidae) management - P.S. Shanmugam; T Srinivasan; V Baskaran; A Suganthi; B Vinothkumar; G Arulkumar; S Backiyaraj; S Chinnadurai; V Somasundaram; N Sathiah; N Muthukrishnan; S.V. Krishnamoorthy; et al. (Plant Protection Science, 2024)
Insecticidal interventions at critical stages of maize are an important strategy for managing invasive insect pest fall armyworm (FAW) Spodoptera frugiperda (J.E. Smith). Conventional spraying systems cannot be used over larger areas, and the insecticide application using unmanned aerial vehicles is becoming popular among peasants. As the FAW resides inside the maize whorls, targeted insecticide application is necessary for effective management. The efficacy of (UAV) spray with different types of nozzles was compared with the conventional spray system, namely high-volume spray and Control droplet applicator. The other spray systems' droplet density, efficacy, and residues of insecticides in plants, soil and water were studied. The UAV droplet density up to 5 m swath recorded no significant variation for both nozzles. A UAV with an atomizer nozzle was as effective as a high-volume spray in reducing the FAW infestation. The residue analysis of leaf samples from the study area revealed more residues in the control droplet applicator and UAV atomizer nozzle. The per cent reduction of initial deposits in the top, middle and bottom maize leaves was least in the UAV atomizer nozzle. The insecticide residues in the study sample area were also below the detectable limit. UAV usage in maize saves time and reduces FAW damage as that of high-volume sprayers.